PERSPECTIVES OF USE OF MANAGEMENT ANALYSIS AND FORECASTING TOOLS FOR MULTIPLE PROFESSIONAL PRODUCTION COMPLEXES - Kolbushkin, Y. P.; Perevozova, I. V.; Andriyishin, N. M.; Kurochkin, K. S. (Scientific Bulletin of Ivano-Frankivsk National Technical University of Oil and Gas (Series: Economics and Management in the Oil and Gas Industry), 2018)
In the article the possibilities analysis of a complex system of managerial analysis of enterprises production and economic activity is conducted and determination of the initial data requirements for its effective application in the conditions of a multiprofile production complex, in particular – to the system of accounting for operating costs, is carried out. The main types of analysis of manufacturing enterprises production and economic activity, as well as key analysis tools are considered. The analysis of key tools and their application prospects in conditions of multiprofile production complexes is carried out. The problems of indicators application in the conditions of consolidation of reporting, and also the influence of the cost accounting system on the efficiency of tools application for the analysis of enterprises production and economic activity are considered. It is established that the existing methods of the production and economic activity analysis, based on standard accounting and reporting documents, allow to determinate the efficiency of enterprises production and economic activity and asset management. It is determined that in conditions of consolidation of activity of multiprofile production complex structural subdivisions the use of modern tools of managerial analysis requires the development of original methods for calculating the profitability of service departments, products (work, services) of which are not the same type. It is proved that subject to compliance the requirements for the system of operating costs accounting the introduction of integrated management analysis will definitely contribute to the enterprises economic development.